A Case of Endobronchial Tuberculosis in Atypical Localization Mimicking Tumor in an Asymptomatic Patient - Çalışkaner Öztürk, Buket; Rekalı Şahin, Hümeyra; Atahan, Ersan; Börekci, Şermin; Batur, Şebnem; Güngördü Mazıcan, Nejdiye; Ferhan Özşeker, Zeynep (Cerrahpaşa Medical Journal, 2022)
Tuberculosis is a disease that can be encountered clinically and radiologically in many different ways. With this feature, it can be confused with many diseases. Endobronchial tuberculosis is defined as a specific inflammation of the tracheobronchial tree caused by the tuberculosis bacillus. Endobronchial tuberculosis can mimic malignancy because of its bronchoscopic and radiological features very similar to bronchial neoplasms. In this article, the approaches followed in the diagnosis of an asymptomatic smoker patient with multifocal mass appearances in the lung were discussed. It was emphasized that endobronchial tuberculosis can mimic lung malignancy in bronchoscopic and radiological aspects and the importance of histopathological diagnosis in case of doubt. Cite this article as: Çalışkaner Öztürk B, Rekalı Şahin H, Atahan E, et al. A case of endobronchial tuberculosis in atypical localization mimicking tumor in an asymptomatic patient. Cerrahpaşa Med J. 2022;46(2):178-180.